POLAROGRAFI DENYUT UNTUK PENENTUAN KADAR EMAS DALAM LARUTAN CAMPURAN DENGAN TEMBAGA DAN PERAK TANPA PROSES PEMISAHAN - Soefjan Tsauri (Jurnal Kimia Terapan Indonesia, 1991)
Pulse Polarographic determination of gold (- 2 ppm) in a solution mixture with the presence of silver and copper ion without separation has been examined. Utilizing the suitable condition, polarographic peaks of gold, silver and copper were separated and thus could make the determination of gold possible in a solution with silver and copper ions. From the investigations carried out, several conclusions were derived i.e. : 1. A system of KOH 1,5M, KN03 0,02 M and KCN 0,01M, which was then called the complexing and supporting electrolyte mixture or "Elektrolit Pendukung Pengkompleks Campuran (EPPC)'; appeared to be capable to remove the interference of copper and silver peaks from the gold polarogram peak area in tile Derivative Pulse Polarography. 2. The capabilities of this EPPC are used to determine the concentration of gold in the range of 2 to 10 ppm. The determination was carried am by the Derivative Pulse Polarography in a solution mixture with 30 ppm of silver and copper ion. Preliminary application of the EPPC system to the analysis of gold in a rock sample was observed and the result was compared with Neutron Activation Analysis method